2017
DOI: 10.4172/2155-9821.1000302
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of Tannin by Bacteria Enterobacter cloacae from the Gut of Indian Mole Cricket (Gryllotalpa krishnani)

Abstract: Insects are the most successful animal on earth; the gut microbes present might play an important role in food digestion as well as the interaction with hosts. In this study insect Gryllotalpa krishnani has been used to isolate the symbiotic associated organisms which play role in host metabolism, promote efficient digestion and to protect the host from the harmful microbes. In the present study, microorganisms were isolated from the gut of G. krishnani and characterized for tannase enzyme activity. It was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It has been observed that MSM media with 0.6% tannic acid at 37 °C promote the most optimal growth. Tannin-digesting bacteria Enterobacter cloacae (Rasiravuthanahalli et al, 2017), Paraburkholderia tropica PKI7, and Kosakonia arachidis PKI8 (Biswas & Mohapatra, 2023) showed maximum growth in MSM media with 0.6% tannic acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that MSM media with 0.6% tannic acid at 37 °C promote the most optimal growth. Tannin-digesting bacteria Enterobacter cloacae (Rasiravuthanahalli et al, 2017), Paraburkholderia tropica PKI7, and Kosakonia arachidis PKI8 (Biswas & Mohapatra, 2023) showed maximum growth in MSM media with 0.6% tannic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Tannase, a ubiquitous and important industrial enzyme in the microbial world, ability to degrade tannins to gallic acid and glucose (Anburaj, 2015). Different Bacterial strains degrading tannic acid were isolated from goat feces (Tahmourespour et al, 2016), ruminal bacteria (Cipriano-salazar et al, 2018), soil (Mohammed, 2016), and gut of Indian Mole Cricket (Rasiravuthanahalli et al, 2017). In this study, Enterobacter hormaechei strain Z8B-60 with the ability of tannic acid degradation was isolated from slaughterhouse waste enriched soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterobacter is common in functional flora of insect gut, such as Bactrocera dorsalis ( 55 , 56 ), S. litura ( 34 ), Spodoptera littoralis ( 57 ), and Gryllotalpa krishnani ( 58 ). Enterobacteriaceae is one of the most widespread families across 30 lepidopteran insects, while the Enterobacter is one of the most common genera ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated from the gut of Indian male cricket (Govindarajan et al, 2017) Exhibits tannase activity, shielding the host insect from the antinutritional action of the plant tannins. One of the three highly abundant bacteria in the gut of diamondback moth, Plutella xylotella (Xia et al, 2017) Metagenomic analysis indicates that they are involved in the production of enzymes involved in amino acid synthesis, digestion of plant products, and detoxification.…”
Section: Enterobacter Cloacaementioning
confidence: 99%